Efektivitas Modul SL Padi Hebat Berbasis ADDIE dalam Meningkatkan Pengetahuan Petani - Roni Jarlis; Juli Supriyanti; Vivi Hendrita; Taufiqqurrahman; Andi Alatas; Fildza Arief Syuhada (LPPM Universitas Malikussaleh - Indonesia, 2026)
Agricultural counseling through Field Schools (SL) has become a strategic approach in improving farmers' knowledge, but its effectiveness is often constrained by the quality of learning modules that are not structured, lack of supporting visuals, and are not accompanied by adequate evaluation instruments.This study aims to analyze the effectiveness of the ADDIE-based Great Rice SL Module in improving farmers' knowledge through a quantitative evaluation approach. The module was applied to 10 farmers participating in the Field School, and the effectiveness of learning was measured using the NGain test, knowledge structure analysis with Principal Component Analysis (PCA), and mapping the relationship between indicators through Pearson correlation. The results showed that the Great Rice SL module was able to increase farmers' knowledge with a medium effectiveness category, as reflected in the NGain value on three core variables: rice cultivation knowledge (0.31), disease identification (0.40), and balanced fertilization (0.41). The PCA analysis showed that the farmer's knowledge structure formed three main latent factors explaining the 26.9%, 19.1%, and 13% variances, respectively related to basic cultivation knowledge, field diagnostic capabilities, and fertilization technical skills. The results of the correlation visualization confirmed the existence of a strong positive relationship between the indicator plates, showing that the increase in knowledge occurred consistently in various aspects measured. Overall, the ADDIE-based SL Padi Hebat module has proven to be effective in increasing farmers' knowledge moderately and consistently, as well as reflecting the relevance of the module in supporting technical learning in the Field School program.